2011
DOI: 10.1002/star.201000134
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of sweetpotato starch

Abstract: Sweetpotato starch is high‐yielding, but has limited development and uses. In this study, physicochemical properties of sweetpotato starch from 11 representative genotypes with diverse geographic origins in China were characterized and showed wide variations. Apparent amylose contents measured by iodine binding ranged from 23.3 to 26.5%, by gel permeation chromatography after debranching from 17.5 to 23.9%, and true amylose content by concanavalin A binding from 15.9 to 22.5%. In vitro digestibility varied fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 30 publications
4
42
1
1
Order By: Relevance
“…The swelling power of SPS at 80°C ranged from 15.69 (Shinwhangmi) to 23.22 g/g (Shinjami), and the solubility ranged from 3.77 (Borami) to 11.01% (Shinjami). When Zhu et al analyzed swelling power and the water solubility index at 85°C, of starches from purple/white fleshed sweet potatoes, the swelling power (13.3–20.4 g/g) showed lower values, but the water solubility index (53.4–85.8%) showed much higher values than our results, though the measuring temperature was 5°C higher than in this study.…”
Section: Resultscontrasting
confidence: 89%
“…The swelling power of SPS at 80°C ranged from 15.69 (Shinwhangmi) to 23.22 g/g (Shinjami), and the solubility ranged from 3.77 (Borami) to 11.01% (Shinjami). When Zhu et al analyzed swelling power and the water solubility index at 85°C, of starches from purple/white fleshed sweet potatoes, the swelling power (13.3–20.4 g/g) showed lower values, but the water solubility index (53.4–85.8%) showed much higher values than our results, though the measuring temperature was 5°C higher than in this study.…”
Section: Resultscontrasting
confidence: 89%
“…Granule surface of starches appeared to be smooth with no sign of any fissure. Zhu et al (2011) also observed smooth granule surface of sweet potato starches without cracks. Most of the sweet potato starch granules were polygonal in shape, however round and irregular shapes were also noted.…”
Section: Resultsmentioning
confidence: 82%
“…Broader range and lower values of melting temperatures of retrograded SPF than native SPF were observed (Table ). The retrograded starch tends to have less perfect crystallinity than the native starch, leading to lower gelatinization temperatures and Δ H . Hence, Δ H of retrograded SPF varied from 1.29 J g −1 dry starch in Gold to 3.62 J g −1 dry starch in OS.…”
Section: Resultsmentioning
confidence: 99%